2019
DOI: 10.3389/fneur.2019.00736
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Elastic Property of Spastic Muscle With Its Joint Resistance Evaluated From Shear Wave Elastography and Biomechanical Model

Abstract: This study aims to quantify passive muscle stiffness of spastic wrist flexors in stroke survivors using shear wave elastography (SWE) and to correlate with neural and non-neural contributors estimated from a biomechanical model to hyper-resistance measured during passive wrist extension. Fifteen hemiplegic individuals after stroke with Modified Ashworth Scale (MAS) score larger than one were recruited. SWE were used to measure Young's modulus of flexor carpi radialis muscle with joint from 0° (at rest) to 50° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
3
9
0
1
Order By: Relevance
“…The NF was validated in people with Parkinson's disease, cerebral palsy and stroke (Gäverth et al, 2014 ; Zetterberg et al, 2015 ; Kachmar et al, 2016 ). Our previously published study confirmed the feasibility to assess muscle stiffness, elasticity and viscosity characteristic of upper extremity spastic muscle in patients with stroke using the NF technique (Leng et al, 2019 ). A systematic review published recently encouraged the application of measuring technique to, including myotonometer, to assess the changes of muscle properties induced by ESW in spastic muscle (Dymarek et al, 2020 ).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The NF was validated in people with Parkinson's disease, cerebral palsy and stroke (Gäverth et al, 2014 ; Zetterberg et al, 2015 ; Kachmar et al, 2016 ). Our previously published study confirmed the feasibility to assess muscle stiffness, elasticity and viscosity characteristic of upper extremity spastic muscle in patients with stroke using the NF technique (Leng et al, 2019 ). A systematic review published recently encouraged the application of measuring technique to, including myotonometer, to assess the changes of muscle properties induced by ESW in spastic muscle (Dymarek et al, 2020 ).…”
Section: Introductionsupporting
confidence: 77%
“…The range of wrist movement was 50° with a starting position at −20° palmar flexion and an end position at 30° extension (7, 21). Three components of NC, EC and VC were calculated based on a biomechanical model which was described in detailed in previous study (Lindberg et al, 2011 ; Pennati et al, 2016 ; Leng et al, 2019 ). EC represents the length-dependent resistant force and VC represents the viscosity-dependent resistant force.…”
Section: Methodsmentioning
confidence: 99%
“…This premise was supported by the differences in muscle density among the tested groups in our current study. The non-invasive ultrasonography method used in the patients with stroke also demonstrated the similar findings on the passive mechanical property changes after the neurological insults ( Jakubowski et al, 2017 ; Leng et al, 2019 ). However, future research involving histological analyses of myofilament and cytoskeleton proteins will be needed to better understand how changes in muscle compositions post-stroke may potentially alter muscle stress/tension.…”
Section: Discussionsupporting
confidence: 54%
“…For example, the inertial sensor or the exoskeleton machine can be used to provide biomechanical information, such as the counter torque and the angle of joint motion in the process of passive stretching [14], [15], [16]. In addition, H-reflex and H/M ratio [17] are determined based on electromyography signals and using Shear Wave Elastography [18], [19] to directly measure muscle stiffness. Although the mechanical signalbased approach has good interpretability, the absence of muscle activation analysis makes it difficult to identify the disturbance caused by contractures.…”
Section: Introductionmentioning
confidence: 99%